A Study Of Flow Induced Vibration At Hydraulic Physical Modellingof Kenyir Dam Spillway - Ali, Abdul Safiq Mohamed (Universiti Sains Malaysia, 2022)
Dams, reservoirs, and other structures like spillways and intake are crucial components of infrastructure for water supply, power generation, storage and flood control, as well as for preventing negative societal and environmental effects that may result from failure, malfunction, or poor design. The design, building, operation, management, safety, and sustainability of dams are all hydraulic issues that are addressed by the hydraulic engineering of dams. This covers all aspects of a structure's hydraulic design, including vibration, vortices, airflow interactions, and dam breaches or wave propagation caused by a dam break. The aim of this study is to study of flow induced vibration at hydraulic physical modelling of Kenyir Dam Spillway. The analysis procedures were carried out using the SCADAS software which is specialized in evaluating vibration effect on structure. Uncontrolled discharge capacity, invalid geometrical properties, unpredictable rainfall leading to extreme floods downstream and also downstream failure because of erosion, sedimentation issues, vortex and the presence of turbulent flow besides the presence of friction were some of the significant factors that led to the reduction in spillway capacity. The results show that both cases model is still capable of withstanding the vibration's magnitude at different frequency since the peak value of magnitude for case Q = 60 L/s and Q = 90 L/s are 2.787 m/s2 and 3.626 m/s2 respectively.